PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS ETNOMATEMATIKA PADA SISWA KELAS VIII SMP KATOLIK ST. ANTONIUS MANADO - Regar, Vivian E.; Lengkong, Yuliana Olivia; Wenas, Jhon Robby (LPPM Politeknik Saint Paul Sorong, 2025)
This research aims to design and develop a learning device in the form of ethnomathematics-based LKPD containing questions and explanations related to local culture that are valid, practical, and effective. The type of research used is Research and Development (R&D) employing the ADDIE model, which consists of the stages of Analysis, Design, Development, Implementation, and Evaluation. The percentage of assessment results obtained from media validators was 92.72%, and the percentage of assessment results from material validators was 96.66%, categorizing them as very valid. Based on the percentage of student responses to the ethnomathematics-based LKPD on the topic of surface area and volume of a cylinder, an average percentage of 91.99% was obtained, categorized as very practical. Furthermore, according to the effectiveness aspect, a student mastery percentage of 85% was obtained, categorized as very effective. Thus, the conclusion of this study is that the development of learning devices, in this case, ethnomathematics-based LKPD on the surface area and volume of cylinders, meets the aspects of validity, practicality, and effectiveness